Liability for illegal tampering with a motor vehicle odometer reading or interference into its proper mileage measurement (Article 306a CC) (Ius Novum, 2019)
The article presents the characteristics of a new type of offence consisting in the alteration of the reading on an odometer of a motor vehicle or interference into its proper measurement of mileage (Article 306a CC). Following a traditional pattern, it describes the development of this institution, the object of protection, types of the offence and its subjective aspect. The article determines the subject and features of the subjective aspect. It also discusses possible concurrence of provisions and penalties involved. The introduction of criminal liability for conduct consisting in illegal tampering with the reading on an odometer is well-grounded, however, the normative approach to the institution is not perfect and does not cover all types of conduct aimed at concealment of actual mileage of a motor vehicle, which can hamper efficient combating the “clocking”. It is in particular noticed that there is a lack of statutory grounds for penalising the replacement of an odometer in order to conceal the actual mileage, which violates the statutory provisions. The separate classification of “commissioning” the activities specified in Article 306a § 1 CC is criticised because it destructs the terminological coherence and the systematic organisation of the Criminal Code.
Keywords: substantive criminal law; altering the reading on an odometer; interference into proper measurement of an odometer; replacement of an odometer